Answer:
B: 5x+5.75
Step-by-step explanation:
2 cones with fruit:
cones= x+x=2x
fruit= $1 x 2=$2
=2x+ 2
3 cones with candy and syrup:
cones= x+x+x=3x
candy= $0.75x3=$2.25
syrup= $0.50x3=$1.50
3x+ (2.25+1.50)
=3x+3.75
both of them together=
(3x+3.75)+(2x+2)= 5x+5.75
Answer:
A) 63.36 years.
B) 100.42 years.
Step-by-step explanation:
We have been given that the population of the world was 7.1 billion in 2013, and the observed relative growth rate was 1.1% per year.
A) Since we know that population increases exponentially, therefore we will use our given information to form an exponential model for population increase and then we will solve for the time by which our population will be double.
![\frac{7.1 \times 2}{7.1} =(1.011)^{t}](https://tex.z-dn.net/?f=%5Cfrac%7B7.1%20%5Ctimes%202%7D%7B7.1%7D%20%3D%281.011%29%5E%7Bt%7D)
![2 =(1.011)^{t}](https://tex.z-dn.net/?f=2%20%3D%281.011%29%5E%7Bt%7D)
Now let us solve for t using logarithm.
![ln(2) =t \cdot ln(1.011)](https://tex.z-dn.net/?f=ln%282%29%20%3Dt%20%5Ccdot%20ln%281.011%29)
![t=\frac{0.6931471805599453}{0.0109399400383344}](https://tex.z-dn.net/?f=t%3D%5Cfrac%7B0.6931471805599453%7D%7B0.0109399400383344%7D)
![t=63.3593217267282743049\approx 63.36](https://tex.z-dn.net/?f=t%3D63.3593217267282743049%5Capprox%2063.36)
Therefore, it will take 63.36 years the population to be double.
B) Now we will find the number of years it will take the population to be triple of its size.
![7.1 \times 3=7.1(1.011)^{t}](https://tex.z-dn.net/?f=7.1%20%5Ctimes%203%3D7.1%281.011%29%5E%7Bt%7D)
![3 =(1.011)^{t}](https://tex.z-dn.net/?f=3%20%3D%281.011%29%5E%7Bt%7D)
Now let us solve for t using logarithm.
![ln(3) =t \cdot ln(1.011)](https://tex.z-dn.net/?f=ln%283%29%20%3Dt%20%5Ccdot%20ln%281.011%29)
![t=\frac{1.0986122886681097}{0.0109399400383344}](https://tex.z-dn.net/?f=t%3D%5Cfrac%7B1.0986122886681097%7D%7B0.0109399400383344%7D)
![t=100.4221490079915311298\approx 100.42](https://tex.z-dn.net/?f=t%3D100.4221490079915311298%5Capprox%20100.42)
Therefore, it will take 100.42 years the population to triple of its size.
Answer:
I think this is right:
50:50
5/10
0.5
50%
Step-by-step explanation:
Answer:
Rectangle
Step-by-step explanation:
According to this grapher that I am using it shows a rectangle using your coordinates
Please give brainliest
Answer:
![T_{3}=27{x}^{2}y^2](https://tex.z-dn.net/?f=T_%7B3%7D%3D27%7Bx%7D%5E%7B2%7Dy%5E2)
Step-by-step explanation:
The given binomial expression is:
![( {x}^{2} + 3y)^{3}](https://tex.z-dn.net/?f=%28%20%7Bx%7D%5E%7B2%7D%20%2B%203y%29%5E%7B3%7D%20%20)
When we compare to:
![{(a +b)}^{n}](https://tex.z-dn.net/?f=%20%7B%28a%20%2Bb%29%7D%5E%7Bn%7D%20)
We have
![a = {x}^{2}](https://tex.z-dn.net/?f=a%20%3D%20%20%7Bx%7D%5E%7B2%7D%20)
![b = 3y \\ n = 3](https://tex.z-dn.net/?f=b%20%3D%203y%20%5C%5C%20n%20%3D%203)
The nth term is given by;
![T_{r+1}=^nC_ra^{n-r}b^r](https://tex.z-dn.net/?f=T_%7Br%2B1%7D%3D%5EnC_ra%5E%7Bn-r%7Db%5Er)
To find the 3rd term, we put:
![r + 1 = 3 \\ r = 2](https://tex.z-dn.net/?f=r%20%2B%201%20%3D%203%20%5C%5C%20r%20%3D%202)
We substitute into the formula to get:
![T_{3}=^3C_2( {x}^{2} )^{3-2}(3y)^2](https://tex.z-dn.net/?f=T_%7B3%7D%3D%5E3C_2%28%20%7Bx%7D%5E%7B2%7D%20%29%5E%7B3-2%7D%283y%29%5E2)
We simply:
![T_{3}=3( {x}^{2} )^{1} \times 9y^2](https://tex.z-dn.net/?f=T_%7B3%7D%3D3%28%20%7Bx%7D%5E%7B2%7D%20%29%5E%7B1%7D%20%5Ctimes%209y%5E2)
![T_{3}=27{x}^{2}y^2](https://tex.z-dn.net/?f=T_%7B3%7D%3D27%7Bx%7D%5E%7B2%7Dy%5E2)